Review Article: Impact of Leishmania spp. on Public Health (Texas Journal of Agriculture and Biological Sciences, 2023)
The genus of Leishmania, intracellular protozoan parasite, Leishmania that belongs to the Trypanosomatida Order under Kinetoplastea Class of Euglenozoa Phylum, includes a large number of species that infect a wide variety of vertebrates and invertebrates, such as rodents and humans resulting in variable clinical manifestations. Taxonomy of the parasite is not fully elucidated, and debate continues not only over the number of species in the subgenus, but also over the definition of species. Leishmaniasis, caused by several different strains of Leishmania, remains a major public health problem globally. The disease is transmitted by mosquitoes and is endemic in mainly arthropod-carrying tropical areas. Due to fast changes in global climate, mosquitoes are expected to expand widely to become more susceptible to disease. There are four main types of disease including cutaneous leishmaniasis (CL), diffuse cutaneous (DCL), mucocutaneous leishmaniasis (MCL) and visceral leishmaniasis (VL) which varies in their characteristics. However, sequalae of the disease based upon the species of parasite and an immune response. With few treatments available, antimonials compounds remain very important in the therapeutic strategies which used most commonly in different areas. However, drug resistance has recently emerged including resistance to the oral therapy for the most recent drug used against VL. This alarming has led to use of non-toxic drugs to treatment of disease and to prescription-related complications. The prospect of widespread drug resistance therefore indicates an urgent need to develop effective new treatments for leishmaniasis. In conclusion, there is a necessary for limiting the complications and preventing death. Additionally, vector control can be implemented wherever possible